EFEKTIVITAS PENGGUNAAN KARTU "BARUANG" SEBAGAI MEDIA PEMBELAJARAN BANGUN RUANG PADA SISWA KELAS V SDN KARUNDANG 1 - Anggi Rahmani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the lack of use of learning media during the learning process carried out by teachers, so that students become bored and lack understanding of the material being taught. The purpose of this research is to develop a Baruang Card (Learning to Build Space) media product based on a scientific approach for learning mathematics of building space materials in grade V of elementary school. The Baruang Card Media will be tested for validity by media experts and maternal experts along with seeing the attractiveness of students This research uses the Research and Development research method of the Borg and Gall development research model with nine steps starting from Research and Information. Collecting. Planning, Develop Preliminary form of Product. Preliminary Field Testing. Operational Field Testing. Operational Product Revision, Main Field Testing, Main Product Revision, and Final Product Revision. This research was conducted at SDN Karundang 1 with the research subject in class V with 16 students in a limited trial and 28 students in a trial use. The results of the study show that the Baruang Card media has been successfully developed and has met the valid criteria of learning media experts, mathematics subject matter experts and teachers with percentages of 97%, 93.33% and 99.6% respectively. Furthermore, the results of the trial of the attractiveness of the Baruang Card media to students also showed that the media produced was attractive by obtaining a percentage of 93.5%. learning media, scientific approach, mathematics building space